Vicini (ma non troppo). Uno studio esplorativo sul tema del vicinato in Italia - Manzo, Lidia (2013)
This paper is an exploratory analysis on the role of neighbours and informal neighbour support in Italy. To be more precise, we have investigated two aspects: at the individual level, we studied the perception of neighbours, while at the family level, we were interested in understanding what kind of supportive relationships can be established between neighbours. In the first part, we develop our theoretical framework, describing a number of factors that can influence the form and content of the neighbourly relationship, citing some results. In the second part, we use data from the Indagine Multiscopo Istat conducted in the year 2003. Regarding the level of neighbours perception, results from binomial logistic regression models indicate that, within the same socio-demographic characteristics and place of residence, there is an effect exerted by urban dimension and level of education. Urban dimension appears to have a negative effect on positive neighbours perception. However, we also found that the higher the level of education, the more likely to have a positive perception of neighbours, and this effect is higher in metropolitan areas compared to other urban areas. Interestingly, supportive relationships among Italian families who experience housing proximity, represent not only an undemanding attitude, but also an infrequent one.